2011
DOI: 10.1152/ajpregu.00085.2011
|View full text |Cite
|
Sign up to set email alerts
|

SR59230A, a beta-3 adrenoceptor antagonist, inhibits ultradian brown adipose tissue thermogenesis and interrupts associated episodic brain and body heating

Abstract: Brown adipose tissue (BAT) thermogenesis occurs episodically in an ultradian manner approximately every 80-100 min during the waking phase of the circadian cycle, together with highly correlated increases in brain and body temperatures, suggesting that BAT thermogenesis contributes to brain and body temperature increases. We investigated this in conscious Sprague-Dawley rats by determining whether inhibition of BAT thermogenesis via blockade of beta-3 adrenoceptors with SR59230A interrupts ultradian episodic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
(67 reference statements)
3
17
0
Order By: Relevance
“…Our findings are similar to those reported previously in rats (Ootsuka et al, 2009, Blessing et al, 2012. Thus, the present data is consistent with the view that the ultradian alternation of rest-active states is a fundamental part of animal life (Aschoff and Gerkema, 1985, Ootsuka et al, 2011, Blessing et al, 2012, 2013.Previous studies, using EEG-based wake-sleep scoring, show robust changes in behavioural and physiological parameters upon waking (Mochizuki et al, 2006, Zhang et al, 2007, Bastianini et al, 2011, Lo Martire et al, 2012, Silvani et al, 2014, Bastianini et al, 2015. Zhang and colleagues performed simultaneous recording of different behavioural and physiological parameters in mice, including EEG and food intake, observed that eating occurs approximately 15 min after waking (Zhang et al, 2007).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Our findings are similar to those reported previously in rats (Ootsuka et al, 2009, Blessing et al, 2012. Thus, the present data is consistent with the view that the ultradian alternation of rest-active states is a fundamental part of animal life (Aschoff and Gerkema, 1985, Ootsuka et al, 2011, Blessing et al, 2012, 2013.Previous studies, using EEG-based wake-sleep scoring, show robust changes in behavioural and physiological parameters upon waking (Mochizuki et al, 2006, Zhang et al, 2007, Bastianini et al, 2011, Lo Martire et al, 2012, Silvani et al, 2014, Bastianini et al, 2015. Zhang and colleagues performed simultaneous recording of different behavioural and physiological parameters in mice, including EEG and food intake, observed that eating occurs approximately 15 min after waking (Zhang et al, 2007).…”
supporting
confidence: 94%
“…It is proposed that, in addition to circadian patterning, ultradian (<24 hour) alternation between active interaction with the external environment and rest is a fundamental part of animal life (Aschoff and Gerkema, 1985, Ootsuka et al, 2011, Blessing et al, 2012, 2013, Blessing and Ootsuka, 2016. The ultradian pattern, also referred to as the basic-rest activity cycle (Kleitman, 1982), is particularly prominent when the circadian pattern is eliminated by destruction of the suprachiasmatic nucleus (Baker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we observed the resident rat for at least 24 h, recording the coordinated behavioral and physiological events that occur when the rat engages with the external environment as part of the basic rest-activity cycle (2,3,46,47). This enabled us to introduce the intruder rat when temperatures were at a basal level.…”
Section: Bat Thermogenesis Contributes To Emotional Hyperthermiamentioning
confidence: 99%
“…To further assess the possible contribution of BAT thermogenesis to emotional hyperthermia, we determined whether SR59230A, a ␤3 adrenoceptor antagonist (33,43,47), reduces the increases in BAT, body, and brain temperatures in resident rats suddenly confronted with an intruder rat. In all resident rats we also monitored the thermoregulatory vascular bed by continuously measuring tail artery blood flow with a chronically implanted Doppler ultrasonic flow probe.…”
mentioning
confidence: 99%